Evaluación del proceso de colonización y degradación de polietileno de baja densidad por inóculo de Aspergillus Niger en humus y compostaje doméstico (2021)
The research focused on the evaluation of the colonization and degradation of low-density polyethylene through the interaction with the inoculum Aspergillus niger in the composting system. Initially, a comprehensive literature search was conducted to characterize LDPE according to its physical, chemical, mechanical, thermal, electrical, and optical properties. Likewise, a search was carried out on the degradation and biodegradation systems of the polymer, and the optimal conditions for the biodegradation process to be efficient. Finally, the results of the experimental process developed during 1 month are presented, in compost bins with humus (mature compost) and fresh compost in the absence and presence of UV radiation.